Analysis of Junior High School Students’ Representational Ability on Comparative Subject Based on Gender - Dewi Anita Sari; Sonya Fanny Tauran (JPMI (Jurnal Pendidikan Matematika Indonesia), 2023)
The study aims to which is a quantitative descriptive research, is to examine the ability of junior high school students to represent mathematical concepts comparatively, based on their gender. The participants were students in 7th grade at Cimindi Advent Middle School during the 2023/2024 academic year, with a total of 20 female and 19 male students. The research utilized a test to evaluate the mathematical representation abilities of the students. The collected data was analyzed by using techniques as data reduction, data presentation, and drawing conclusions. The findings of the study revealed that the average mathematical representation ability score of the female students was 45.42%, while the average score of male students was 34.06%. Female and male students can represent mathematically on the subject of comparison in the low category. But when viewed from gender, three female students are in high sort with average of 76.85%. In medium category, there are two people with average of 66.67%, and in low class, there are 15 people with an average – average 36.30%. There is one male student with a high ability with average of 75%. In the medium category, there are three people with average of 61.11%, and in the low sort, there are 15 people with an average of 25.93%. While the overall results for KRM were based on indicators of female visual representation 42.5% and male visual representations 31.6%, while the overall results for KRM were based on hands of representation of female mathematical equations/expressions 39% and representation of male mathematical equations/expressions 39.5%, and the overall result for KRM based on indicators of representation of written words/texts for women is 46.7% and model for words/written texts for men is 25.9%. Based on the overall results of female and male students for KRM based on indicators, there is no difference in the low category.